A modular, human body-mimicking phantom with active thermoregulation capabilities for validation and verification of convective hyperthermia devices - L. Van den Bossche; W. Vertessen; J. Van den Bossche; O. Rudenko; J. Bogers; L. Brancato (International Journal of Hyperthermia)
Objectives This study aims to design and fabricate a modular phantom for hyperthermia applications, addressing interpatient variability in thermal regulation mechanisms like sweating rate, metabolic heat production, and blood redistribution.Materials & methods The phantom can be constructed in various weights and dimensions by connecting identical units. Each unit consists of an agar-based block, an ethyl cellulose-based top layer, a heat source, deep and superficial water circulation, and a sweating mechanism. Agar and ethyl cellulose gels mimic the thermal properties of human tissues and fat respectively. The blocks are wrapped in PVC foil to prevent water evaporation. A heating wire, coiled around an embedded aluminum tubing simulates metabolic heat production. A superficial water circulation mimics skin capillaries. A water pump ensures a steady flow rate throughout the tubing system. Sweat production is simulated using a water pump and perforated tubing. A programmed controller maintains core temperature in a normal operating mode and simulates an anesthetized patient in anesthesia mode.Results Temperature uniformity and regulation were assessed under varying environmental conditions. The phantom effectively regulated its core temperature at 37.0 °C +/- 0.7 °C with an ambient temperature ranging between 21 °C and 30 °C. Activating the water circulation reduced the maximum temperature gradient within the phantom from 4.70 °C to 1.92 °C.Conclusion The versatile phantom successfully models heat exchange processes. Its thermal properties, dimensions, and heat exchange rates can be tuned to mimic different patient models. These are promising results as an effective tool for hyperthermia device validation and verification, representing human physiological responses.